The English riots of 2011 : a summer of discontent - Briggs, Daniel (Criminologist) (Waterside Press, 2012)
From Facebook, Twitter, BlackBerry and gossip to hard facts, research and empirical investigation, this outstanding collection looks at the nature and causes of the English Riots of 2011 one year after they occurred. Though worrying in their nature, speed and scale, the book points out that rioting is nothing new - even if technological advances have altered their 'organization', the way in which the police respond and the incessant nature of media coverage. From 'moral panics' to 'broken Britain' and anxieties about youth crime, the book looks at various flashpoints of the riots such as the killing of Mark Duggan by police marksmen, the widespread looting, the political and criminal justice responses and a growing discontent about the current neoliberal order. The book rejects Coalition Prime Minister David Cameron's much-publicized assertion that these events were 'criminality, pure and simple', just as it counters attempts to lay blame on sections of the community or 'outsiders'. Looking at phenomena such as 'shopping for free' and the idea that the lawlessness represented some kind of instant carnival, it concentrates on how order was restored and individuals fast-tracked via police cells and courts into harsh sentences as well as issues of marginality, hopelessness, political and economic corruption and media distortions. Wide-ranging and expert in its analysis, it also considers the modern-day global context for riots as well as comparing Brixton 1981 and other iconic events of the past. Further highlights include: the role of new social media in terms of recruitment, resistance, and surveillance; the role of the urban street gang; gender, racialization, resentment, post-riot rhetoric and the profiling the 2011 rioters. It looks at how the riots spread to other cities in the UK including Manchester, Liverpool and Birmingham - as well as examining events and attitudes in places such as Spain, Greece, and those of the Arab Spring.